Sweat-absorbing quick-drying fabric and preparation process thereof

By using a combined structure of polyester fiber layer and wet-conducting layer in the fabric, and using materials such as polyvinyl formaldehyde, sodium alginate and polyvinylidene fluoride, the problem of difficulty in absorbing and discharging sweat after exercise is solved, the effect of rapid sweat absorption and quick drying is achieved, and the comfort and antibacterial properties of the fabric are improved.

CN119704832APending Publication Date: 2025-03-28SUZHOU CHINT ENTERPRISE DEV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411882892.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing fabrics are difficult to absorb and discharge sweat in time after exercise, causing clothing to adhere to the body surface and affecting human body functions.

Method used

The combined structure of a polyester fiber layer and a wet conduction layer is adopted. The wet conduction layer is made of polyvinyl formaldehyde, sodium alginate and polyvinylidene fluoride. The polyester fiber layer is treated with dopamine treatment and silica modification.

Benefits of technology

The fabric is quickly absorbed and quickly dry, reducing the time difference between sweat secretion and transmission, and improving the fabric's comfort and antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005198616940000091
    Figure BDA0005198616940000091
Patent Text Reader

Abstract

The invention relates to a sweat-absorbent quick-dry fabric and a preparation process thereof.The sweat-absorbent quick-dry fabric comprises a polyester fiber layer and a moisture conducting layer, the moisture conducting layer comprises polyvinyl formal, sodium alginate and polyvinylidene fluoride, and the polyester fiber layer comprises dopamine-treated polyester fibers and silicon dioxide modified components. According to the prepared fabric, the sweat absorption performance of the fabric can be promoted, sweat is evaporated to dryness in time, and therefore the quick-drying effect is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fabrics, and in particular to a sweat-absorbing and quick-drying fabric and a preparation process thereof. Background Art

[0002] Fabric is the material used to make clothing. As one of the three elements of clothing, fabric can not only interpret the style and characteristics of clothing, but also directly influence the color and shape of the clothing.

[0003] The heat generated by human body metabolism during exercise is quickly dissipated through the sweat secreted by the sweat glands in the skin and evaporates; however, after exercise, if the sweat cannot evaporate in time, not only will the clothes stick to the surface of the body, but it will also affect the body's functions. Summary of the invention

[0004] In order to improve the moisture absorption and quick-drying performance of fabrics, the present application provides a sweat-absorbing and quick-drying fabric and a preparation process thereof.

[0005] The present application provides a sweat-absorbing and quick-drying fabric and a preparation process thereof using the following technical solutions: In the first aspect, the present application provides a sweat-absorbing and quick-drying fabric, which adopts the following technical solution: A sweat-absorbing quick-drying fabric comprises a polyester fiber layer and a moisture-conducting layer, wherein the moisture-conducting layer comprises polyvinyl formal, sodium alginate and polyvinylidene fluoride, and the polyester fiber layer comprises dopamine-treated polyester fibers and a silicon dioxide-modified component.

[0006] By adopting the above technical scheme, a moisture-conducting layer is arranged on one side of the polyester fiber layer. The moisture-conducting layer has a unidirectional moisture-conducting property, can reduce the time difference between sweat secretion and transmission, and quickly conduct sweat to the outermost layer for evaporation in time, thereby improving the sweat absorption and quick-drying performance of the fabric; the moisture-conducting layer is prepared by polyvinyl formal, sodium alginate and polyvinylidene fluoride. Polyvinyl formal has good mechanical properties and biocompatibility. It is a polymer material obtained by the acetal reaction of hydroxyl and aldehyde groups of polyvinyl alcohol and formaldehyde under strong acidic conditions. It has good hydrophilicity and is insoluble in water, so as to further improve the hygroscopicity of the fabric, thereby improving the comfort performance of the fabric. Sodium alginate and polyvinylidene fluoride are also added to the fabric. Polyvinylidene fluoride is used as a hydrophobic base, and sodium alginate is distributed on the polyvinylidene fluoride to obtain a moisture-conducting layer, which further improves the transmission speed of sweat; the polyester fiber layer is prepared by dopamine-treated polyester fiber and silica-modified components, so that the polyester fiber layer has good hydrophobic properties, which further improves the sweat-wicking performance of the fabric.

[0007] Preferably, the polyvinyl formal is prepared by the following method: Mix polyvinyl alcohol with water, stir until the polyvinyl alcohol is completely dissolved, and spin to obtain a polyvinyl alcohol fiber membrane; mix polyvinyl pyrrolidone, formaldehyde and water, seal and stir until uniform to obtain a reaction liquid; apply the reaction liquid to the surface of the polyvinyl alcohol fiber membrane, add concentrated hydrochloric acid around the polyvinyl alcohol fiber membrane, seal and react, wash to remove free formaldehyde and polyvinyl pyrrolidone, and dry to obtain polyvinyl alcohol formal.

[0008] By adopting the above technical scheme, the formaldehyde reaction liquid of the coated polyvinyl pyrrolidone reacts with the polyvinyl alcohol fiber membrane during the penetration process to form a gradual acetal degree gradient, thereby obtaining polyvinyl alcohol formal. Such a wettability gradient is conducive to promoting the rapid transfer of sweat so that the sweat can be discharged quickly. The acetal reaction does not change the crystallinity of polyvinyl pyrrolidone, and introduces aldehyde groups, reducing the hydroxyl content. The polyvinyl alcohol fiber membrane is converted to hydrophobic, further improving the moisture absorption and perspiration performance of polyvinyl formal.

[0009] Preferably, the mass ratio between the polyvinyl alcohol and formaldehyde is 1:(0.4-0.5).

[0010] By adopting the above technical solution, preferably the mass ratio between polyvinyl alcohol and formaldehyde is within the above range, the stability of the prepared polyvinyl formal can be further improved.

[0011] Preferably, the moisture conductive layer is prepared by the following method: After mixing polyvinylidene fluoride, N,N-dimethylformamide and acetone, the mixture is stirred to obtain a polyvinylidene fluoride spinning solution, and the polyvinylidene fluoride is spun on the hydrophilic side of polyvinyl formal to obtain a polyvinylidene fluoride composite fiber membrane; sodium alginate and water are mixed and stirred to obtain a sodium alginate solution, and the sodium alginate solution is applied to the polyvinylidene fluoride side of the polyvinylidene fluoride composite membrane, and finally the residual solvent and moisture are removed by drying to obtain a moisture conductive layer.

[0012] By adopting the above technical scheme, a hydrophobic polyvinylidene fluoride composite fiber membrane is used as a hydrophobic substrate on the outer layer of polyvinyl formal, and sodium alginate is coated on the surface of the polyvinylidene fluoride composite fiber membrane. The hydrophobic force of the hydrophobic layer on the sweat transmitted through the polyvinylidene fluoride composite fiber membrane to the hydrophilic points of sodium alginate can be reduced, thereby increasing the sweat discharge rate. At the same time, during the spinning process, the volatility of acetone is higher than that of N,N-dimethylformamide. When acetone evaporates, grooves are formed on the surface of the polyvinylidene fluoride composite fiber membrane, which is beneficial to improving the hydrophobic properties of the polyvinylidene fluoride composite fiber membrane, and further improving the moisture absorption and quick-drying properties of the prepared fabric.

[0013] Preferably, the concentration of sodium alginate in the sodium alginate solution is 1.8-2.2 wt %.

[0014] By adopting the above technical solution, the concentration of sodium alginate in the sodium alginate aqueous solution is preferably within the above range, which can further improve the comprehensive performance of the prepared moisture conductive layer.

[0015] Preferably, the silica-modified composite component comprises silica and a composite quaternary ammonium salt.

[0016] Preferably, the silicon dioxide modified component is prepared by the following method: N,N-dimethylformamide, N,N-dimethyloctadecyl and γ-chloropropyltriethoxysilane are mixed, stirred until the components are dissolved, potassium iodide is added, the temperature is increased and stirred, and excess N,N-dimethylformamide is removed by vacuum distillation, and the compound quaternary ammonium salt is obtained by cooling. Ethyl orthosilicate, water, ethanol and ammonia water are mixed and stirred, the compound quaternary ammonium salt is added, and the mixture is refluxed, washed and centrifuged, and dried to obtain a silica modified component.

[0017] By adopting the above technical scheme, N,N-dimethyloctadecylamine, N,N-dimethylformamide and γ-chloropropyltriethoxysilane are compounded to prepare a quaternary ammonium salt, and the quaternary ammonium salt is grafted onto silica. The prepared silica-modified composite component has good hydrophobic properties, which can further improve the quick-drying and perspiration-wicking properties of the fabric. At the same time, the prepared silica-modified composite has good antibacterial properties and can effectively prevent the attachment of bacteria, thereby making the fabric have good antibacterial properties.

[0018] Preferably, the mass ratio between the quaternary ammonium salt and tetraethyl orthosilicate is 1:(1.8-2.2).

[0019] By adopting the above technical solution, preferably the mass ratio between the quaternary ammonium salt and the ethyl orthosilicate is within the above range, the stability of the prepared silicon dioxide composite component can be further improved.

[0020] Preferably, the polyester fiber layer is prepared by the following method: After mixing Tris buffer, copper sulfate and dopamine hydrochloride to obtain a dopamine solution, the polyester fiber is immersed in the dopamine solution, and then hydrogen peroxide is added, stirred for reaction and then washed to obtain dopamine-treated polyester fiber, octadecylamine and a silica-modified component are mixed with water, and then the dopamine-treated polyester fiber is added, stirred for reaction, washed after reaction, dried and spun and woven to obtain a polyester fiber layer.

[0021] By adopting the above technical solution, dopamine has good biocompatibility and good adhesion performance. After treating the polyester fiber, the binding performance of the silica composite component can be improved. At the same time, the generated polydopamine also has hydrophobic properties, which further improves the hydrophobic properties of the fabric, thereby improving the moisture absorption and quick-drying properties of the fabric. In the second aspect, the present application provides a preparation process for a sweat-absorbing and quick-drying fabric, which adopts the following technical solution: A preparation process of a sweat-absorbing and quick-drying fabric comprises the following steps: The modified polyester fiber layer is laminated to one side of the sodium alginate moisture conductive layer, and then the layers are sewn together to obtain a sweat-absorbing and quick-drying fabric.

[0022] In summary, the present application includes at least one of the following beneficial technical effects: 1. In the present application, a moisture conductive layer is arranged on one side of the polyester fiber layer. The moisture conductive layer has a unidirectional moisture conductive property and can reduce the time difference between sweat secretion and transmission, and discharge sweat in time, thereby improving the sweat absorption and quick-drying performance of the prepared fabric. The moisture conductive layer is prepared by polyvinyl formal, sodium alginate and polyvinylidene fluoride. Polyvinyl formal has good biocompatibility and good hydrophilicity, which can further improve the moisture absorption performance of the fabric. 2. Using the polyvinylidene fluoride composite fiber membrane as the hydrophobic base on the outer layer of polyvinyl formal, and then coating sodium alginate on the surface of the polyvinylidene fluoride composite fiber membrane, can reduce the hydrophobic force of the hydrophobic layer on the sweat transmitted to the hydrophilic points of sodium alginate through the polyvinylidene fluoride composite fiber membrane, thereby increasing the sweat discharge rate, thereby improving the sweat absorption and quick-drying properties of the fabric; 3. The surface of the polyester fiber is treated with dopamine, and then the silica composite component is combined with the treated polyester fiber surface, so that the hydrophobic properties of the polyester fiber are further improved. At the same time, the polyester fiber has good antibacterial properties, and the moisture absorption and perspiration discharge properties and antibacterial properties of the prepared sweat-absorbing and quick-drying fabric are improved. DETAILED DESCRIPTION

[0023] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained commercially; Example 1 Preparation of polyvinyl formal: 36 g of polyvinyl alcohol was mixed with 264 g of deionized water. After heating to 90 °C, the mixture was stirred at 200 r / min until the polyvinyl alcohol was completely dissolved. The mixture was allowed to stand and cool naturally to room temperature. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 20 kV, and the injection rate was 1 mL h. -1The spinning distance was 15 cm, and a fiber membrane with a thickness of 1 mm was prepared by electrospinning. The spun fiber membrane was heat-treated in an oven at 160°C for 10 min to obtain a polyvinyl alcohol fiber membrane.

[0024] Mix 20g of polyvinyl pyrrolidone, 14.4g of formaldehyde and 50g of deionized water solution, seal and stir at a speed of 200r / min for 3h until uniform to obtain a reaction solution, spread the polyvinyl alcohol fiber membrane, evenly apply the reaction solution to the surface of the polyvinyl alcohol fiber membrane, and drop 10mL of concentrated hydrochloric acid around the polyvinyl alcohol fiber membrane. After sealing, react in an oven at 30°C for 8h. After the reaction, wash repeatedly with deionized water to remove free formaldehyde and polyvinyl pyrrolidone, and dry in an oven at 50°C to remove moisture to obtain polyvinyl formal.

[0025] Preparation of moisture conducting layer: 5 g of polyvinylidene fluoride, 31.5 g of N,N-dimethylformamide and 13.5 g of acetone were mixed and stirred at a speed of 200 r / min for 8 h. After stirring, the mixture was allowed to stand to remove bubbles to obtain a polyvinylidene fluoride spinning solution. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 18 kV, and the injection rate was 0.8 mL h -1 , the spinning distance is 15 cm, polyvinylidene fluoride is electrospun on the hydrophilic side of polyvinyl formal to obtain a polyvinylidene fluoride composite fiber membrane; sodium alginate is mixed with deionized water and stirred evenly to obtain a sodium alginate solution with a concentration of 1.8wt%, the inner diameter of the needle is set to 0.2mm, the applied voltage is 16kV, and the injection rate is 0.8mLh -1 The sodium alginate solution was sprayed onto the polyvinylidene fluoride side of the polyvinylidene fluoride composite membrane at a spraying distance of 10 cm and a roller speed of 150 r / min. Finally, the membrane was dried in a vacuum oven at 60° C. to remove residual solvent and moisture to obtain a moisture conductive layer.

[0026] Preparation of silica modified component: After mixing 450 g of N,N-dimethylformamide, 50.16 g of N,N-dimethyloctadecyl and 36.87 g of γ-chloropropyltriethoxysilane, stir at a speed of 200 r / min until the components are dissolved, then add 12 g of potassium iodide, heat to 100°C, stir at a speed of 300 r / min for 24 hours, remove excess N,N-dimethylformamide by reduced pressure distillation, and cool to room temperature to obtain a composite quaternary ammonium salt.

[0027] 19.29 g of tetraethyl orthosilicate, 20 g of deionized water, 80 g of ethanol and 4 g of ammonia water were mixed, stirred at 200 r / min for 4 h at room temperature, 10.71 g of composite quaternary ammonium salt was added to the solution, refluxed at 80° C. for 2 h, and finally washed and centrifuged alternately with deionized water and ethanol for 3 times, and dried in a vacuum drying oven to obtain a silica modified component.

[0028] Preparation of modified polyester fiber: After mixing Tris buffer, 2 mM copper sulfate and dopamine hydrochloride, a dopamine solution containing 2 mg / mL dopamine hydrochloride was obtained, and the polyester fiber was immersed in the dopamine solution with a bath ratio of 1:100. Subsequently, 2 mM hydrogen peroxide was added, and the reaction was stirred at a temperature of 60°C for 24 hours, and then ultrasonically cleaned in deionized water to obtain a polydopamine composite polyester fiber. After mixing 32 g of octadecylamine, 4.8 g of a silica modified component and 800 g of deionized water, the dopamine composite polyester fiber was added, and the reaction was stirred at a temperature of 60°C. After the reaction, ethanol and deionized water were used for alternating washing for 3 times, and the modified polyester fiber was obtained after drying.

[0029] Prepare sweat-wicking and quick-drying fabrics: The modified polyester fiber is woven to obtain a modified polyester fiber layer, and the modified polyester fiber layer is attached to one side of the moisture conductive layer of sodium alginate, and then stitched to obtain a sweat-absorbing and quick-drying fabric.

[0030] Example 2 Preparation of polyvinyl formal: 36 g of polyvinyl alcohol was mixed with 264 g of deionized water. After heating to 90 °C, the mixture was stirred at 200 r / min until the polyvinyl alcohol was completely dissolved. The mixture was allowed to stand and cool naturally to room temperature. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 20 kV, and the injection rate was 1 mL h. -1 The spinning distance was 15 cm, and a fiber membrane with a thickness of 1 mm was prepared by electrospinning. The spun fiber membrane was heat-treated in an oven at 160°C for 10 min to obtain a polyvinyl alcohol fiber membrane.

[0031] Mix 20g of polyvinyl pyrrolidone, 18g of formaldehyde and 50g of aqueous solution, seal and stir at a speed of 200r / min for 3h until uniform to obtain a reaction solution, spread the polyvinyl alcohol fiber membrane, evenly apply the reaction solution to the surface of the polyvinyl alcohol fiber membrane, and drop 10mL of concentrated hydrochloric acid around the polyvinyl alcohol fiber membrane. After sealing, react in an oven at 30°C for 8h. After the reaction, wash repeatedly with deionized water to remove free formaldehyde and polyvinyl pyrrolidone, and dry in an oven at 50°C to remove moisture to obtain polyvinyl formal.

[0032] Preparation of moisture conducting layer: 5 g of polyvinylidene fluoride, 31.5 g of N,N-dimethylformamide and 13.5 g of acetone were mixed and stirred at a speed of 200 r / min for 8 h. After stirring, the mixture was allowed to stand to remove bubbles to obtain a polyvinylidene fluoride spinning solution. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 18 kV, and the injection rate was 0.8 mL h -1 , the spinning distance is 15 cm, polyvinylidene fluoride is electrospun on the hydrophilic side of polyvinyl formal to obtain a polyvinylidene fluoride composite fiber membrane; sodium alginate is mixed with deionized water and stirred evenly to obtain a sodium alginate solution with a concentration of 2.2wt%, the inner diameter of the needle is set to 0.2mm, the applied voltage is 16kV, and the injection rate is 0.8mLh -1 The sodium alginate solution was sprayed onto the polyvinylidene fluoride side of the polyvinylidene fluoride composite membrane at a spraying distance of 10 cm and a roller speed of 150 r / min. Finally, the membrane was dried in a vacuum oven at 60° C. to remove residual solvent and moisture to obtain a moisture conductive layer.

[0033] Preparation of silica modified component: After mixing 450 g of N,N-dimethylformamide, 50.16 g of N,N-dimethyloctadecyl and 36.87 g of γ-chloropropyltriethoxysilane, stir at a speed of 200 r / min until the components are dissolved, then add 12 g of potassium iodide, heat to 100°C, stir at a speed of 300 r / min for 24 hours, remove excess N,N-dimethylformamide by reduced pressure distillation, and cool to room temperature to obtain a composite quaternary ammonium salt.

[0034] After mixing 20.625 g of tetraethyl orthosilicate, 20 g of deionized water, 80 g of ethanol and 4 g of ammonia water, the mixture was stirred at 200 r / min at room temperature for 4 h, 9.375 g of composite quaternary ammonium salt was added to the solution, and the mixture was refluxed at 80° C. for 2 h. Finally, the mixture was washed and centrifuged alternately with deionized water and ethanol for 3 times, and dried in a vacuum drying oven to obtain a silica modified component.

[0035] Preparation of modified polyester fiber: After mixing Tris buffer, 2 mM copper sulfate and dopamine hydrochloride, a dopamine solution containing 2 mg / mL dopamine hydrochloride was obtained, and the polyester fiber was immersed in the dopamine solution with a bath ratio of 1:100. Subsequently, 2 mM hydrogen peroxide was added, and the reaction was stirred at a temperature of 60°C for 24 hours, and then ultrasonically cleaned in deionized water to obtain a polydopamine composite polyester fiber. After mixing 32 g of octadecylamine, 4.8 g of a silica modified component and 800 g of deionized water, the dopamine composite polyester fiber was added, and the reaction was stirred at a temperature of 60°C. After the reaction, ethanol and deionized water were used for alternating washing for 3 times, and the modified polyester fiber was obtained after drying.

[0036] Prepare sweat-wicking and quick-drying fabrics: The modified polyester fiber is woven to obtain a modified polyester fiber layer, and the modified polyester fiber layer is attached to one side of the moisture conductive layer of sodium alginate, and then stitched to obtain a sweat-absorbing and quick-drying fabric.

[0037] Example 3 Preparation of polyvinyl formal: 36 g of polyvinyl alcohol was mixed with 264 g of deionized water. After heating to 90 °C, the mixture was stirred at 200 r / min until the polyvinyl alcohol was completely dissolved. The mixture was allowed to stand and cool naturally to room temperature. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 20 kV, and the injection rate was 1 mL h. -1 The spinning distance was 15 cm, and a fiber membrane with a thickness of 1 mm was prepared by electrospinning. The spun fiber membrane was heat-treated in an oven at 160°C for 10 min to obtain a polyvinyl alcohol fiber membrane.

[0038] Mix 20g of polyvinyl pyrrolidone, 16.2g of formaldehyde and 50g of aqueous solution, seal and stir at a speed of 200r / min for 3h until uniform to obtain a reaction solution, spread the polyvinyl alcohol fiber membrane, evenly apply the reaction solution to the surface of the polyvinyl alcohol fiber membrane, and drop 10mL of concentrated hydrochloric acid around the polyvinyl alcohol fiber membrane. After sealing, react in an oven at 30°C for 8h. After the reaction, wash repeatedly with deionized water to remove free formaldehyde and polyvinyl pyrrolidone, and dry in an oven at 50°C to remove moisture to obtain polyvinyl formal.

[0039] Preparation of moisture conducting layer: 5 g of polyvinylidene fluoride, 31.5 g of N,N-dimethylformamide and 13.5 g of acetone were mixed and stirred at a speed of 200 r / min for 8 h. After stirring, the mixture was allowed to stand to remove bubbles to obtain a polyvinylidene fluoride spinning solution. The inner diameter of the needle was set to 0.8 mm, the applied voltage was 18 kV, and the injection rate was 0.8 mL h -1 , the spinning distance was 15 cm, polyvinylidene fluoride was electrospun on the hydrophilic side of polyvinyl formal to obtain a polyvinylidene fluoride composite fiber membrane; sodium alginate was mixed with deionized water and stirred evenly to obtain a sodium alginate solution with a concentration of 2 wt%, the inner diameter of the needle was set to 0.2 mm, the applied voltage was 16 kV, and the injection rate was 0.8 mL h -1 The sodium alginate solution was sprayed onto the polyvinylidene fluoride side of the polyvinylidene fluoride composite membrane at a spraying distance of 10 cm and a roller speed of 150 r / min. Finally, the membrane was dried in a vacuum oven at 60° C. to remove residual solvent and moisture to obtain a moisture conductive layer.

[0040] Preparation of silica modified component: After mixing 450 g of N,N-dimethylformamide, 50.16 g of N,N-dimethyloctadecyl and 36.87 g of γ-chloropropyltriethoxysilane, stir at a speed of 200 r / min until the components are dissolved, then add 12 g of potassium iodide, heat to 100°C, stir at a speed of 300 r / min for 24 hours, remove excess N,N-dimethylformamide by reduced pressure distillation, and cool to room temperature to obtain a composite quaternary ammonium salt.

[0041] After mixing 20 g of tetraethyl orthosilicate, 20 g of deionized water, 80 g of ethanol and 4 g of ammonia water, the mixture was stirred at 200 r / min at room temperature for 4 h, 10 g of composite quaternary ammonium salt was added to the solution, and the mixture was refluxed at 80° C. for 2 h. Finally, the mixture was washed and centrifuged alternately with deionized water and ethanol for 3 times, and dried in a vacuum drying oven to obtain a silica modified component.

[0042] Preparation of modified polyester fiber: After mixing Tris buffer, 2 mM copper sulfate and dopamine hydrochloride, a dopamine solution containing 2 mg / mL dopamine hydrochloride was obtained, and the polyester fiber was immersed in the dopamine solution with a bath ratio of 1:100. Subsequently, 2 mM hydrogen peroxide was added, and the reaction was stirred at a temperature of 60°C for 24 hours, and then ultrasonically cleaned in deionized water to obtain a polydopamine composite polyester fiber. After mixing 32 g of octadecylamine, 4.8 g of a silica modified component and 800 g of deionized water, the dopamine composite polyester fiber was added, and the reaction was stirred at a temperature of 60°C. After the reaction, ethanol and deionized water were used for alternating washing for 3 times, and the modified polyester fiber was obtained after drying.

[0043] Prepare sweat-wicking and quick-drying fabrics: The modified polyester fiber is woven to obtain a modified polyester fiber layer, and the modified polyester fiber layer is attached to one side of the moisture conductive layer of sodium alginate, and then stitched to obtain a sweat-absorbing and quick-drying fabric.

[0044] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, 10.8 g of formaldehyde is used in preparing polyvinyl formal.

[0045] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, 21.6 g of formaldehyde is used in preparing polyvinyl formal.

[0046] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that in Example 6, when preparing the moisture conductive layer, the concentration of sodium alginate in the sodium alginate solution is 1.5 wt %.

[0047] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that in Example 7, when preparing the moisture conductive layer, the concentration of sodium alginate in the sodium alginate solution is 2.5 wt %.

[0048] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, 18 g of ethyl orthosilicate and 12 g of composite quaternary ammonium salt are used in preparing the silicon dioxide modified component.

[0049] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, when preparing the silicon dioxide modified component, 21.43 g of ethyl orthosilicate and 8.57 g of the composite quaternary ammonium salt are used.

[0050] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the modified polyester fiber in Example 10, the silica modified component is replaced with ordinary silica.

[0051] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the modified polyester fiber in Example 11, dopamine hydrochloride is not added.

[0052] Comparative Example 1 Comparative Example 1 is based on Example 3, and the moisture-conducting layer in Comparative Example 1 is only polyvinyl formal.

[0053] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the modified polyester fiber is replaced by ordinary polyester fiber.

[0054] Performance testing The samples of Examples 1-11 and Comparative Examples 1-2 were sampled and the following performance tests were performed: (1) Antibacterial performance test Taking "GBT 20944.1-2007 Evaluation of antibacterial properties of textiles Part 1: Agar plate diffusion method" as the detection standard, the antibacterial tops prepared in the embodiments and comparative examples were sampled to obtain 10 cm*10 cm fabric samples, and the antibacterial performance test was carried out. Each sample was tested 3 times, and the average value was filled in Table 1.

[0055] (2) Hydrophobic performance test The contact angle of the prepared sample surface was tested. Three points were randomly selected on both sides of each sample for testing, and the test was performed three times. After taking the average value, the test results were filled in Table 1.

[0056] (3) Evaporation rate test Using "Evaluation of Moisture Absorption and Quick-drying Properties of Textiles (Part 1): Single Combined Test Method (GB / T 21655.1-2008)" as the test standard, add 0.2g of sweat to the center of a sample with a specification of 10cm×10cm, hang it in an environment with a temperature of 22℃ and a humidity of 50%, and evaporate naturally. Record the weight every 5 minutes until the sample mass maintains a constant weight, calculate the evaporation rate, and fill in Table 1.

[0057] Table 1 Performance test results of Examples 1-11 and Comparative Examples 1-2 Combined with Table 1, it can be seen that the antibacterial rates of Escherichia coli and Staphylococcus aureus of the samples of Examples 1-3 are both 99.1% and above, indicating that the sweat-absorbing and quick-drying fabric prepared by the present application has good antibacterial properties; the hydrophobic angles of the samples of Examples 1-3 are all 142° and above, and the evaporation rates are all 0.41gh -1 The above indicates that the quick-drying fabric prepared in the present application has good hydrophobic properties and has the performance of rapid moisture absorption and drying.

[0058] The mass ratios of formaldehyde to polyvinyl alcohol in Examples 4 and 5 are not within the range defined in the present application. When the formaldehyde content is too much or too little, the reaction between the hydroxyl group and the aldehyde group is difficult to promote, and the stability of the obtained polyvinyl formal product is reduced. It is difficult to improve the sweat discharge and evaporation performance of the moisture-conducting layer. Therefore, the hydrophobic angle and evaporation rate of Examples 4 and 5 are reduced.

[0059] In Example 6 and Example 7, when preparing the moisture conductive layer, the concentration of sodium alginate in the sodium alginate solution is not within the range specified in the present application. When the concentration of sodium alginate is too low, it is difficult to form hydrophilic points on the surface of the moisture conductive layer, and it is difficult to further promote the discharge of sweat, thereby affecting the evaporation rate of the fabric; when the concentration of sodium alginate is too high, sweat reaches saturation after evaporating to the outermost layer and reverse osmosis occurs, so that a large amount of sweat will still remain on the skin surface, making it difficult to discharge the sweat, affecting the hydrophobicity and sweat absorption and quick-drying performance of the fabric, so the evaporation rates of Example 6 and Example 7 are both reduced.

[0060] In Example 8 and Example 9, when preparing the silica-modified component, the mass ratio between tetraethyl orthosilicate and the composite quaternary ammonium salt is not within the scope defined in the present application. When the content of tetraethyl orthosilicate is too little, it is difficult to form more silica microspheres, making it difficult to increase the particle size of silica, and it is difficult to improve the roughness of the fiber surface. Therefore, the hydrophobicity of the polyester fiber is difficult to improve, and the evaporation rate is also affected. After the content of silica decreases, it is difficult to further promote the antibacterial properties of the fabric; when the content of tetraethyl orthosilicate is too much, too much silica is formed, so that the particle size of silica is too large, and silica agglomerates in the system, affecting the stability of silica when attached to the surface of the polyester fiber; therefore, the various performances of Example 8 and Example 9 are reduced.

[0061] In Example 10, when preparing the modified polyester fiber, the silica-modified component is replaced with ordinary silica. The hydrophobic angle of the unmodified silica is difficult to be further improved, and the dispersibility of silica is difficult to improve. The compatibility and stability in the system are reduced, thereby affecting the performance of the fabric.

[0062] In Example 11, dopamine hydrochloride was not added when preparing the modified polyester fiber. The adhesion performance of the fiber not treated with dopamine decreased, and the binding performance between the silica modified component and the polyester fiber also decreased. Therefore, the stability of the polyester fiber decreased, affecting the comprehensive performance of the prepared fabric.

[0063] In Comparative Example 1, the moisture-conducting layer is only polyvinyl formal, and the fabric obtained by combining polyvinyl formal and the polyester fiber layer is difficult to improve the effect of sweat discharge from the fabric due to the adhesion of water, so that the comprehensive performance of the fabric is reduced.

[0064] In Comparative Example 2, when preparing the polyester fiber layer, the modified polyester fiber was replaced with ordinary polyester fiber. The roughness of the polyester fiber surface that was not treated with the composite component of dopamine and silica was difficult to improve, the hydrophobic angle of the prepared polyester fiber layer was difficult to further improve, and the antibacterial performance was also reduced. Therefore, all performances of Comparative Example 2 were reduced.

[0065] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A sweat-absorbing and quick-drying fabric, characterized in that: The invention comprises a polyester fiber layer and a moisture conductive layer, wherein the moisture conductive layer comprises polyvinyl formal, sodium alginate and polyvinylidene fluoride, and the polyester fiber layer comprises dopamine treated polyester fiber and a silicon dioxide modified component.

2. The sweat-absorbing and quick-drying fabric according to claim 1, characterized in that: The polyvinyl formal is prepared by the following method: Mix polyvinyl alcohol with water, stir until the polyvinyl alcohol is completely dissolved, and spin to obtain a polyvinyl alcohol fiber membrane. Mix polyvinyl pyrrolidone, formaldehyde and water, seal and stir until uniform to obtain a reaction liquid, apply the reaction liquid to the surface of the polyvinyl alcohol fiber membrane, add concentrated hydrochloric acid around the polyvinyl alcohol fiber membrane, seal and react, wash to remove free formaldehyde and polyvinyl pyrrolidone, and dry to obtain polyvinyl alcohol formal.

3. The sweat-absorbing and quick-drying fabric according to claim 2, characterized in that: The mass ratio between the polyvinyl alcohol and formaldehyde is 1:(0.4-0.5).

4. The sweat-absorbing and quick-drying fabric according to claim 3, characterized in that: The moisture conducting layer is prepared by the following method: After mixing polyvinylidene fluoride, N,N-dimethylformamide and acetone, the mixture is stirred to obtain a polyvinylidene fluoride spinning solution, and the polyvinylidene fluoride is spun on the hydrophilic side of polyvinyl formal to obtain a polyvinylidene fluoride composite fiber membrane; sodium alginate is mixed with water, the mixture is stirred to obtain a sodium alginate solution, and the sodium alginate solution is applied to the polyvinylidene fluoride side of the polyvinylidene fluoride composite membrane, and finally the residual solvent and moisture are removed by drying to obtain a moisture conductive layer.

5. The sweat-absorbing and quick-drying fabric according to claim 4, characterized in that: The concentration of sodium alginate in the sodium alginate solution is 1.8-2.2 wt %.

6. The sweat-absorbing and quick-drying fabric according to claim 1, characterized in that: The silicon dioxide modified composite component comprises silicon dioxide and a composite quaternary ammonium salt.

7. The sweat-absorbing and quick-drying fabric according to claim 6, characterized in that: The silicon dioxide modified component is prepared by the following method: N,N-dimethylformamide, N,N-dimethyloctadecyl and γ-chloropropyltriethoxysilane are mixed, stirred until the components are dissolved, potassium iodide is added, the temperature is increased and stirred, and excess N,N-dimethylformamide is removed by vacuum distillation, and the compound quaternary ammonium salt is obtained by cooling. Ethyl orthosilicate, water, ethanol and ammonia water are mixed and stirred, the compound quaternary ammonium salt is added, and the mixture is refluxed, washed and centrifuged, and dried to obtain a silica modified component.

8. The sweat-absorbing and quick-drying fabric according to claim 7, characterized in that: The mass ratio between the quaternary ammonium salt and tetraethyl orthosilicate is 1:(1.8-2.2).

9. The sweat-absorbing and quick-drying fabric according to claim 1, characterized in that: The polyester fiber layer is prepared by the following method: After mixing Tris buffer, copper sulfate and dopamine hydrochloride to obtain a dopamine solution, the polyester fiber is immersed in the dopamine solution, and then hydrogen peroxide is added, stirred for reaction and then washed to obtain dopamine-treated polyester fiber, octadecylamine and a silica-modified component are mixed with water, and then the dopamine-treated polyester fiber is added, stirred for reaction, washed after reaction, dried and spun and woven to obtain a polyester fiber layer.

10. A method for preparing the sweat-absorbing and quick-drying fabric according to any one of claims 1 to 9, characterized in that: The steps include: The modified polyester fiber layer is laminated to one side of the sodium alginate moisture conductive layer, and then the layers are sewn together to obtain a sweat-absorbing and quick-drying fabric.

Citation Information

Patent Citations

  • Nanoparticles containing organosilicon quaternary ammonium salt and preparation method and application of nanoparticles

    CN107694522A

  • Double-layer composite unidirectional-dampness guiding and antibacterial fabric

    CN110356062A

  • Preparation method of high-flux polytetrafluoroethylene composite nanofiltration membrane

    CN111804162A

  • Mineral composite moisture absorption fiber textile and preparation method thereof

    CN114481602A

  • Rapid moisture-conducting and sweat-discharging fiber material and preparation method thereof

    CN115976734A